2008
DOI: 10.1007/s12289-008-0380-x
|View full text |Cite
|
Sign up to set email alerts
|

Direct spinning of carbon nanotube fibres from liquid feedstock

Abstract: Carbon nanotubes are regarded by many as being the next generation in high performance materials due to their unique properties. The Cambridge Process was developed to utilize these unique properties by directly spinning carbon nanotube fibres drawn from an aerogel sock. The sock is formed from carbon nanotubes grown via a catalytic chemical vapour deposition (CVD) process. Due to the nature of CVD, the process is readily scalable. Kilometres of fibre can be made at a rate of 20 m/min. Altering process paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…3 shows the cross section and surface (inset) SEM images of the prepared membrane. MWCNTs and SWCNTs (π-π interaction) are stronger than those with the polymer matrix [45,46]. Therefore pristine SWCNTs and MWCNTs tend to agglomerate, do not distribute well and form a micron level sponge structure within PIM-1 matrix.…”
Section: Morphology 341 Effect Of Pristine Swcnts Mwcnts and mentioning
confidence: 99%
“…3 shows the cross section and surface (inset) SEM images of the prepared membrane. MWCNTs and SWCNTs (π-π interaction) are stronger than those with the polymer matrix [45,46]. Therefore pristine SWCNTs and MWCNTs tend to agglomerate, do not distribute well and form a micron level sponge structure within PIM-1 matrix.…”
Section: Morphology 341 Effect Of Pristine Swcnts Mwcnts and mentioning
confidence: 99%
“…It is worth noting that, as reported in the literature, pristine CNTs are usually found to be not well dispersed in different polymer matrices. 16,17 Carbon nanotubes possess an extremely high tensile modulus (50-1000 GPa), [18][19][20] tensile strength (20-150 GPa) [21][22][23] and high aspect ratio (tipically ca. 300-1000).…”
Section: Resultsmentioning
confidence: 99%
“…From our previous work [9][10][11][12][13], the general trend observed in this process is that an increase in temperature causes a change in the type of CNT grown, from single to multi-walled, as well as an exponential increase in the amount of carbon deposited. It has been previously shown that for temperatures above 1100…”
Section: Effect Of Process Parameters On the Deposited Filmmentioning
confidence: 93%